Developing the Cognitive Competence of Future Teachers Through A Motivational Approach - Abdumanopov Muhammadsodiq Muhammadyusuf ugli (European International Journal of Pedagogics, 2025)
This article explores the relevance, theoretical foundations, and practical aspects of developing the cognitive competence of future teachers based on a motivational approach within modern pedagogical education. The study employed theoretical analysis, diagnostic tools, and experimental methods to examine the role of motivation in enhancing students’ cognitive competence. The findings demonstrate that a motivational approach has a significant positive impact on the development of critical thinking, problem-solving, and independent learning skills among pedagogical students.